The Effects of Shakespeare’s The Comedy of Errors on Tanpinar’s The Time Regulation Institute - Sacide Akcan (Şarkiyat Mecmuası)
Ahmet Hamdi Tanpınar described William Shakespeare as the greatest poet of all time and encouraged Turkish writers and poets to be nourished by his artistic genius and the multicultural structure of his works. Tanpınar himself also benefited from Shakespeare’s fictions and from the characters in his works. The Time Regulation Institute has a special place among Tanpınar’s works in that it contains social satire and is a novel about cultural crisis. In this novel, Tanpınar benefited from both the general atmosphere as well as certain fictional features of Shakespeare’s The Comedy of Errors. Just as the romantics in France had found Shakespeare and his works to be suitable for their own purposes and benefited from them, the pioneering intellectuals of Turkish literature such as Nâmık Kemâl and Ahmet Hamdi Tanpınar also paid special attention to Shakespeare’s works during the change Turkish society underwent in order to spread the theater genre and get to know Western culture more closely. Tanpınar made references to Shakespeare’s works and characters in his poems, stories, and novels. Despite not directly mentioning Shakespeare or his works in The Time Regulation Institute, the novel is reminiscent of The Comedy of Errors in terms of its general atmosphere. In addition, many common features are found between the two works, such as lost jewelry, accusations of theft and insanity, a mental and spiritual doctor, and complicated and ridiculous events that occurred due to similar names. The first part of this study examines the effects Shakespeare has had on Turkish literature and Tanpınar, while the second part first introduces The Time Regulation Institute and The Comedy of Errors before going on to compare the common aspects of the two works and attempting to clarify Shakespeare’s influence on Tanpınar’s artistic personality.